Business continuity management: From literature framework to practical application in Vietnamese small and medium-sized enterprises - Pham, Tien Trung (Edelweiss Applied Science and Technology, 2026)
Empirical data analysis from 128 selected Vietnamese SMEs indicated that the firms have experienced losses and disruptions in their business activities during turbulent times. Along with that, the paper identified the major reasons, not only unexpected changes in business environments but also deficiencies in risk and crisis management in these Vietnamese enterprises. A widely accepted crisis management model, Business Continuity Management (BCM), is defined as a “holistic management process that identifies potential threats to an organization and the impacts to business operations those threats, if realized, might cause” [1]. This paper reviews literature on risk and crisis management and introduces BCM as a crisis management approach and as a practical framework. Consequently, the necessity of applying the BCM model/approach to Small and Medium-sized Enterprises (SMEs) in Vietnam has been confirmed. Finally, the paper suggests major recommendations for successfully applying the BCM model toward sustainable development in these firms, such as developing a business continuity plan and organizing a BCM structure.